2005
DOI: 10.1021/jo051334f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Substituted α-Amino Acids via Lewis Acid Promoted Enantioselective Radical Conjugate Additions

Abstract: [Chemical reaction: See text] Lewis acid promoted radical conjugate additions to beta-substituted alpha,beta-unsaturated alpha-nitro esters and amides were investigated. With achiral Lewis acids, there was competition between the desired radical conjugate addition and undesired alkene reduction mediated by Bu3nH. Zinc Lewis acids provided the greatest amounts of addition products with both substrate classes. Studies with Bu3nD indicated that the acidic alpha-stereocenter of the alpha-nitro ester products does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Similar chemistry has been explored by Castle in order to synthesize b-substituted a-amino acids (Scheme 71). 191 The reaction is highly sensitive to a range of factors including the nature of the bsubstituent on the acceptor 254, which must be aromatic in order to obtain good yields. The properties of the various activating groups must be balanced for good yields and stereoselectivity; amides are plagued by reduction of the alkene, whilst their ester counterparts are untainted by this side reaction.…”
Section: Stereoselective Radical Conjugate Addition Reactionsmentioning
confidence: 99%
“…Similar chemistry has been explored by Castle in order to synthesize b-substituted a-amino acids (Scheme 71). 191 The reaction is highly sensitive to a range of factors including the nature of the bsubstituent on the acceptor 254, which must be aromatic in order to obtain good yields. The properties of the various activating groups must be balanced for good yields and stereoselectivity; amides are plagued by reduction of the alkene, whilst their ester counterparts are untainted by this side reaction.…”
Section: Stereoselective Radical Conjugate Addition Reactionsmentioning
confidence: 99%
“…The presence of Bu 3 SnH for hydride trapping of the intermediate radical also causes the formation of reduction products, though this can be minimized by use of zinc Lewis acids. Chiral ligands such as bisoxazolines can produce moderate levels of enantioselection in the obtained α -nitro esters, which are converted into the corresponding α -amino acid derivatives by simple catalytic hydrogenation (Scheme 3.10 ) [26,27] . More traditionally, β -substituted α , β -unsaturated α -nitro esters 11 can add organolithium and Grignard reagents to give the corresponding α -nitro esters 12 , which are amenable to further functionalization at the reactive 2 -position (Scheme 3.11 ) [28] .…”
Section: Amino Acid Derivativesmentioning
confidence: 99%
“…Initial attempts to add radicals to α-methyl-β-acyloxy oxazolidinones, however, gave negligible reactivity (< 10%); but greatly improved reactivity results when an N -H imide template lacking the A 1,3 strain is used, making possible a highly diastereo-and enantioselective method for the preparation of anti-propionate aldol-like products 158 (Scheme 42). Mg(ClO 4 ) 2 -19 was used as the chiral Lewis acid and with all three radicals A recent report by Castle and coworkers describes the synthesis of β-substituted α-amino acids through an enantioselective conjugate radical addition followed by H-atom transfer [133]. A screening of Lewis acids and chiral ligands revealed that a combination of Mg(NTf 2 ) 2 and DBFOX/Ph-164 provided the best yields and enantioselectivities (Scheme 43).…”
Section: Scheme 39 Acetate Aldols By Enantioselective Conjugate Radicmentioning
confidence: 99%